Impact of the COVID-19 Pandemic on Physical and Mental Health in Lower and Upper Middle-Income Asian Countries: A Comparison Between the Philippines and China - Tee, Michael (Frontiers Media S.A., 2022)
10.3389/fpsyt.2020.568929